2020
DOI: 10.1111/cdoe.12524
|View full text |Cite
|
Sign up to set email alerts
|

Understanding oral health help‐seeking among Middle Eastern refugees and asylum seekers in Australia: An exploratory study

Abstract: Objectives:Andersen's behavioural model of healthcare utilization is one of the most commonly used frameworks for help-seeking across a broad range of health areas, including oral health. The Model has been used in a wide range of previous studies to explore and understand oral health service use among both general populations and ethnic minorities. However, no research has explored its utility in understanding refugees' and asylum seekers' oral health help-seeking. As such, this study aimed to improve underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Similar to this result, a previous publication from a refugee camp in Jordan found that pain is the chief complaint among patients inside the camp, and they only come to the dental clinic when they have severe pain (21,22). Moreover, treatment provided were mostly extraction because most of the patients visit the dental clinic in late stages of the problem when nothing can be done to save the tooth (14,23). Other treatments included different kinds of llings, the rst stage of root canal treatment, uoride, scaling, and many other basic dental treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to this result, a previous publication from a refugee camp in Jordan found that pain is the chief complaint among patients inside the camp, and they only come to the dental clinic when they have severe pain (21,22). Moreover, treatment provided were mostly extraction because most of the patients visit the dental clinic in late stages of the problem when nothing can be done to save the tooth (14,23). Other treatments included different kinds of llings, the rst stage of root canal treatment, uoride, scaling, and many other basic dental treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Intake and engagement 36 Competing priorities 23 39 Medication characteristics 39 Unmet need 31 Distinction between problem recognition, decision to seek help and decision to use healthcare system 74 Dental service use and dental experiences 57 Psychosocial factors 28 Patient and transition 36 Fear 23 Reminder strategies 39 Medication adherence strategies 36 (Mis)trust 23 90 Personal emergency alarm system 31 Billing 36 Previous experiences 23 90 Informal care system 31 Avoidant strategies 54 Intended and actual use 28 57 Situation and satisfaction of the next of kin 80 Specific programme for support 36 Contingency plans for future falls 31 Characteristics at the level of informal caregivers 37 : Physician referral, knowledge about the services, acculturation Health Literacy 36 Health literacy 39 54 90 Mental health 85 Individualised care 36 Characteristics at the level of informal caregivers 37 : Familism, perception about services, religiosity, gender roles Spirituality 54 Service experience 57 Vulnerability factors 71 Philosophical approaches 36 Pharmacy services 39 Rheumatologist 90 Conscientiousness 90…”
Section: Need Factorsmentioning
confidence: 99%
“…To date, several studies [10][11][12] exist analyzing the factors associated with dental service use based on the Andersen model [6] mainly showing that predisposing characteristics, enabling resources (depending on the healthcare system) and need factors (such as oral health-related quality of life [13,14]) can determine dental service use.…”
Section: Introductionmentioning
confidence: 99%